Species profiles life histories and environmental requirements of coastal fishes and invertebrates (South Florida)--Snook - Seaman, William, Jr.; Collins, Mark. (Washington, D.C. U.S. Department of the Interior, 1983)
FWS/OBS-82/11.16
Keywords: Invertebrates; Fishes; History; Snook--South Florida